A global MPPT technique for PV systems under partial shading conditions - Celikel, Resat (Taylor & Francis Ltd, 2024)
Maximum Power Point Tracking (MPPT) algorithms are used to obtain maximum power from PV (Photovoltaic) systems in variable atmospheric conditions. Partial shading conditions (PSCs) have an important effect causing the maximum power points of PV systems to change. In this study, a new hybrid MPPT algorithm was proposed by combining Voltage Scanning (VSC) and Cuckoo Search Algorithm (CSA) methods to obtain maximum power from a PV system running under PSC. To test the proposed method, a 252.6 kW grid-connected PV system with 609 panels, including 7 serial panels and 87 parallel strings, was created in the MATLAB/Simulink environment. This system was tested under 10 different PSCs by using VSC, Particle Swarm Optimization (PSO), CSA, and the proposed MPPT methods. The average tracking efficiency and speed of the proposed method under these conditions were obtained as 99.74% and 0.3s, respectively. Under PSCs, the proposed method achieved the highest tracking efficiency of 99.92%, while the highest tracking speed that it achieved was 0.22s. On the other hand, the superiority of the proposed hybrid MPPT algorithm was clearly demonstrated by comparing it to the VSC, PSO, and CSA methods.
Keywords: Solar energy; partial shading; hybrid MPPT; voltage scanning; Cuckoo Search Algorithm